Mark Twain [videorecording (DVD)] - Burns, Ken, 1953-; Duncan, Dayton; Ward, Geoffrey C.; David, Keith; Holbrook, Hal; Miller, Arthur, 1915-2005; Styron, William, 1925-2006; Conway, Kevin; Bosco, Philip (Florentine Films ; PBS, 2001)
Recounts Mark Twain's life told primarily through his own words. Includes interviews with Hal Holbrook, Arthur Miller, William Styron and many others.